Asbestos: not just an exhibit at the Smithsonian - Gerkin, Patrick M. (Critical criminology, 2015)
The Smithsonian Institution operates the largest museum and research complex in the world. In the past 25 years, the Smithsonian Institution has both acted and failed to act in a way that demonstrates a disregard for worker safety in their many facilities. This research examines actions and inactions of the Smithsonian Institution regarding workplace exposure to asbestos. Through a secondary analysis of congressional testimony, citations issued by the Occupational Health and Safety Administration, private reports, and various media accounts of the events, this research seeks to examine the perpetrators’ actions as a crime of omission and offer a theoretical explanation. The explanation attempts to situate the individuals within the micro-, meso-, and macro-level forces that shape motivations and create opportunities for individuals to disregard worker safety and jeopardize human life.